Enhancement of nutritional soy protein and peptide supplementation on skin repair in rats - Jian Zhang; Xiaohang Fu; Wenhui Li; He Li; Zhiwei Ying; Xinqi Liu; Liduan Yin (Journal of Functional Foods, 2020)
The aim of this study was to assess the effect of soy protein and soy peptide on skin repair process in male Wistar rats. Soy protein and soy peptide were administered orally by gavage to the rats post-operatively for 16 days. The supplementation of soy protein and soy peptide resulted in improvement of leucocytes production, decrease in serum inflammation index (IL-1β, IL-6, TNF-α) as well as increase of plasma protein concentration. Additionally, the excessive production of inflammatory factors in peptide group were significantly suppressed compared with the protein group at day 4, which indicated that soy peptide had a better impact on promoting the process of skin repair. Histopathological analysis indicated that peptide group performed better on fibroblast proliferation and collagen synthesis than the protein group, and eventually manifests as more collagen deposition and a better skin repair rate. In conclusion, soy peptide displayed the potential to promote skin regeneration.